Financial crisis and forming of the European monetary fund: Should the European Agreement be changed - Petrović Pero; Živković Aleksandar (Međunarodni Problemi)
In this paper, the authors analyze the possibilities and advantages of realization of the idea of creating the European Monetary Fund, the European equivalent of the IMF. European officials and experts believe that the financial crisis in the European Union, as was the case in Greece, can be successfully solved within the EU institutions. The assistance that the EMF would provide would be stipulated by fulfilment of strict conditions. The ECB, which insists on independence, would join it in establishing this mechanism, since not any has been created so far that would provide financial assistance to members of the Eurozone.